Theoretical study on composition‐dependent properties of ZnO·nAl2O3 spinels. Part II: Mechanical and thermophysical. Issue 12 (13th July 2021) - Xu, Pengyu; Wang, Hao; Ren, Lu; Tu, Bingtian; Wang, Weimin; Fu, Zhengyi
Abstract: Knowledge on the mechanical and thermophysical properties of ZnO· n Al2 O3 is essential for practical applications. Based on the first‐principles calculations and the bond valence method, the disordered spinel‐type structure of ZnO· n Al2 O3 ( n  = 1–4) was constructed to investigate the composition‐dependent mechanical and thermophysical properties. The effects of cation substitution on the hardness, elastic modulus, thermal expansion, and thermal conductivity were revealed from the insights into the chemical bonds. At a higher n, the tetrahedral bond is stronger, manifested as its higher hardness and bulk modulus as well as smaller thermal expansion coefficient. Meanwhile, the octahedral bond is weaker, leading to the lower hardness and bulk modulus, along with the larger expansion coefficient. In consequence, the hardness and elastic moduli of ZnO· n Al2 O3 are improved moderately while the expansion coefficient is decreased with the rise of n . Due to the different vibration characteristics of Zn IV and Al IV, the cation disorder in the 8 a site provides the primary source of phonon scattering, resulting in the dramatic reduction of thermal conductivity as n increases. The understanding offers guidance on the application‐oriented design of new oxide spinels.